The dilatation factor of left atrium in remote period after the mitral valve prosthesis - K. V. Pukas; V. V. Lazoryshynets (Клінічна хірургія)
Objective. Studying of the morphometry indices and contractility of the heart left compartments in the left atrium reduction after prosthesis of a mitral valve.